The Profiles of Long Non-coding RNA and mRNA Transcriptome Reveals the Genes and Pathway Potentially Involved in Pasteurella multocida Infection of New Zealand Rabbits - Hu, Jiaqing; Li, Wenqiang; Huang, Bing; Zhao, Qiaoya; Fan, Xinzhong (Frontiers in Veterinary Science, 2021)
Infection with Pasteurella multocida (P. multocida) causes severe epidemic diseases in rabbits and is responsible for pronounced economic losses in the livestock industry. Long noncoding RNAs (lncRNAs) have been proven to exert vital functions in regulating host immune responses to bacterial attacks. However, little is known about how lncRNAs participate in the rabbit immune response against P. multocida infection in the lungs. Here, LncRNA and mRNA expression profiles were analyzed by transcriptomics and bioinformatics during P. multocida infection. A total of 336 lncRNAs and 7014 mRNAs were differentially expression at 1 day and 3 days post infection (dpi) based on pairwise comparison. Nearly 80% of differentially expressed lncRNAs exhibited an increased expression at 3 dpi suggesting that P. multocida genes are responsible for regulation. GO and KEGG enriched analysis indicated that immune-related pathways were significantly enriched at 3 dpi. Moreover, genes were enriched in process in related to the host immune and inflammatory response, including increase in pattern recognition receptors (PRRs), cytokines and chemokines.These results indicate that the increased immune-related genes may play crucial roles in defending against P. multocida attacks. Overall, these results advance our cognition of the role of lncRNAs and mRNAs in modulating the rabbit innate immune response against P. multocida attacks, which will offer a valuable clue for further studies into exploring P. multocida-related diseases in human.